From Entry to Egress: Strategic Exploitation of the Cellular Processes by HIV-1 - Ramdas, Pavitra; Sahu, Amit Kumar; Mishra, Tarun; Bhardwaj, Vipin; Chande, Ajit (Frontiers in Microbiology, 2020)
HIV-1 employs a rich arsenal of viral factors throughout its life cycle and co-opts intracellular trafficking pathways. This exquisitely coordinated process requires precise manipulation of the host microenvironment, most often within defined subcellular compartments. The virus capitalizes on the host by modulating cell-surface proteins and cleverly exploiting nuclear import pathways, and the ribosomal machinery, among other key processes. Successful virus-cell interactions are indeed crucial in determining the extent of infection. By evolving defenses against host restriction factors, while simultaneously exploiting host dependency factors, the life cycle of HIV-1 presents a fascinating montage of an ongoing host-virus arms-race. Herein, we provide an overview of how HIV-1 exploits native functions of the host cell and discuss recent findings that fundamentally change our understanding of the post-entry replication events.